The Role of Parents in Providing Sex Education to Preschool Children - Utami, Tri; Kurniawati, Erna Yovi; Azka, Arlina (Agribiohealth (Journal of Agriculture, Biology & Health Sciences), 2024)
Violence against women in Indonesia is dominated by cases of sexual violence. Sex education in early childhood is needed to give children an understanding of the anatomy of the human reproductive organs in a simple and understandable way. This study aims to determine the role of parents in providing sex education in early childhood or preschool. This study uses a quantitative descriptive design with a cross-sectional design. The research was conducted at Masyithoh Ngasem Nursery School on 44 children who were purposively selected. Parental role was measured using a questionnaire. The data were analysed univariately. The results showed that most of the parents (90.21%) had provided good sex education to their children. In addition to explaining the genital organs, parents must be able to give examples and teach children to tell their parents if someone else touches their genitals. Sex education in early childhood is expected to prevent child sexual abuse and other sexual crimes. Children who know will be able to avoid, refuse and tell their parents if they are confronted with conditions that are suspected to lead to sexual crimes.